Preliminary proposal of environmental and conservation flows of the ecosystem of the Zaza river downstream of Zaza dam (Cuba) - García Láinez, Diana; Jiménez-Gavilán, Pablo (My University, 2017)
The mangrove’s forest that its situated on Zaza’s mouth (or estuary), localizated in Sancti Spiritus province (Cuba) it has seen deteriorated in the last 40 years because of the construction of Zaza’s dam. This dam regulate the natural floods of the river and displace a constant ecological flow during the 12 months of the year. Through the project "Study and improvement of the planning and management of water resources in the Zaza river basin (Cuba). Definition of policies and strategies for adaptation to the future impacts of global climate change (ESGEREHIZA) " between the Universities of Málaga and Sancti Spíritus, it was intended to study the dam's impact on the delta area, analyzing existing data and methodologies currently applied. In cooperation with the protection entities, management and use of the water resources of Cuba, the regulations established for the calculation of sanitary expenditure established in the Zaza river were studied, being determined insufficient for the maintenance of adequate conditions of life, both fishery and the associated flora. Based on data from the Zaza’s dam hydrograph, the Tennant method was used to estimate the ecological flows. The results show the possibility of applying the three criteria of this methodology to obtain an ecological flow that achieves excellent habitat conditions. On the other hand, studying the current deterioration of the mouth zone, a preliminary proposal was made for generating water flow that would help the regeneration of the ecosystem.
Keywords: Ecología de estuarios - Zaza (Río, Cuba); Ecological flow; Generator flow; Hydrological resource; Mangrove